Lethality of Suicidal Organophosphorous Poisoning in Karachi in 2010 (Medical Forum Monthly, 2024)
Objective: The study was aimed to evaluate the cases of suicide using organophosphorous compounds as intoxicant with the objective to bring up possible preventive measures based upon modifiable factors associated with lethality.Design: Cross-sectional analytical Study.Materials and Methods: This retrospective study was based upon 66 patients of poisoning treated at intensive care unit of Ward No.5, JPMC Karachi during a period of one year from January 2010 to December 2010.Results: Out of total 66 cases of poisoning 38 were of organophosphorous compounds (OPC) poisoning, 20 males and 18 females. Most of the cases (63%) of OPC poisoning were in age range of 20-40 years, 33 (86.84 %) were of suicidal poisoning while 5 (13.16%) had accidental poisoning and 57 % reported to treatment facility within 6 hours. Conclusions & recommendations: All the cases of OPC poisoning had severe symptoms with fatal out come. Suicidal ratio was quite high. The period between the ingestion of poison and initiation of treatment plays vital role. In order to reduce fatality rate urgent intervention is required by government by improving the treatment facilities at local level hospitals i.e. primary health care centres and banning of highly toxic organophosphorous compounds. Additional measures which can help include improving the public awareness regarding recognition of toxic symptoms & importance of prompt referral to an appropriate facility.